Implementation of Blended Learning in the New Normal Period Using Audiovisual Media, Kahoot and Googleform in Elementary School - Sukayati, Siti (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
This research was motivated by the low understanding of the third grade students of SDN Trompo Kendal. The pre-cycle results can be seen from 16 students, only 10 students have completed the KKM. The percentage of completeness is only 62.5%.The objectives of this study are: (1) To determine the effect of applying the blended learning model. (2) To determine the increase in student understanding through the blended learning model.This study used Classroom Action Research (CAR) with the Kemmis and Taggart model which consisted of 4 stages, namely planning, acting, observing, and reflecting which were carried out in 3 cycles. The subjects of this study were students of class III SDN 2 Trompo Kendal with a total of 16 students. Data collection was carried out using tests, observation, documentation and tests.The results of this study indicate that: (1) In the student activity in the first cycle the student activity got a score of 87.5% (Good) in the second cycle a score of 93.75% (Very Good). 2) The results show that classical learning completeness has reached the specified indicator, namely> 80%, so this learning can be said to be successful.